Genetic Diversity of Decapoda in the Indo-Pacific Region: A Literature Review - Ronal Kurniawan; Nur Ikhlas Syuhada (South East Asian Marine Sciences Journal, 2026)
The Indo-Pacific region is the global center of marine biodiversity, home to more than 30% of the world's marine species. The order Decapoda, which comprises more than 17,000 species, plays significant ecological and economic roles in this region. This literature review aims to synthesize current knowledge on the genetic diversity and population structure of Decapoda in the Indo-Pacific and to identify the factors influencing these patterns. Molecular studies employing genetic markers such as mitochondrial DNA (mtDNA), microsatellites, and genomic sequencing indicate that Indo-Pacific Decapoda populations generally exhibit high haplotype diversity with relatively low nucleotide differentiation. Several factors, including larval dispersal capability, the duration of the planktonic phase, geographic and oceanographic barriers, and local adaptation to environmental conditions, shape population structure. Anthropogenic activities, particularly overexploitation, have led to declines in effective population size and genetic erosion in several commercially important species, such as Penaeus monodon and Scylla serrata. This review highlights the importance of integrating genetic data into sustainable fisheries management, including ecosystem-based stock assessment, periodic genetic monitoring, and the incorporation of genetic considerations in aquaculture and restocking programs to ensure the long-term sustainability of Decapoda populations in the Indo-Pacific region.